Enzyme profiling of a range of sugarcane tissue types with different levels of sucrose - Orendo-Smith, R. (Stellenbosch : University of Stellenbosch, 2006)
Thesisa (MSc (Genetics. Plant Biotechnology))--University of Stellenbosch, 2005.